Standard Risk Aversion and the Demand for Risky Assets in the Presence of Background Risk - Günter Franke; Richard C. Stapleton; Marti G. Subrahmanyam (University of Konstanz, Center of Finance and Econometrics (CoFE), 2000)
We consider the demand for state contingent claims in the presence of a zero-mean, nonhedgeable background risk. An agent is defined to be generalized risk averse if he/she reacts to an increase in background risk by choosing a demand function for contingent claims with a smaller slope. We show that the conditions for standard risk aversion: positive, declining absolute risk aversion and prudence are necessary and sufficient for generalized risk aversion. We also derive anecessary and suÆcient condition for the agent's derived risk aversion to increase with a simple increase in background risk.
urn:nbn:de:bsz:352-opus-6213
Keywords: 330; Optionspreistheorie; Anlageverhalten; Risikoaversion; Risiko; Theorie